Hubungan Komunikasi Terapeutik Bidan Terhadap Kepuasan Ibu Hamil Dalam Pelayanan Antenatal Care (ANC) - Irawati Jufri (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Therapeutic communication is one of the professional competencies that midwives must possess in providing antenatal care (ANC) services. Effective therapeutic communication can establish a trusting relationship between midwives and pregnant women, improve comfort during healthcare services, and contribute to improving service quality and patient satisfaction. This study aimed to analyze the relationship between midwives' therapeutic communication and the level of satisfaction among pregnant women with antenatal care (ANC) services at Tempe Primary Health Center. This study was an observational analytic study using a cross-sectional approach. The sample consisted of 33 pregnant women selected using a purposive sampling technique. Data were collected using a midwives' therapeutic communication questionnaire and a pregnant women's satisfaction questionnaire, then analyzed using univariate and bivariate analyses with the Chi-square test at a significance level of 95% (α = 0.05). The results showed that most respondents assessed the midwives' therapeutic communication as good (22 respondents; 66.7%), while the majority of pregnant women were satisfied with the antenatal care services (25 respondents; 75.8%). The Chi-square test showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between midwives' therapeutic communication and the level of satisfaction among pregnant women with antenatal care (ANC) services at Tempe Primary Health Center. It was concluded that midwives' therapeutic communication was associated with the level of satisfaction among pregnant women receiving antenatal care (ANC). Therefore, therapeutic communication should be maintained and improved to enhance the quality of midwifery services.